Tackling workplace bullying: A scholarship of engagement study of workplace wellness as a system. Issue 6 (4th December 2017) - Georgakopoulos, Alexia; Kelly, Michael P.
Abstract : Purpose: The purpose of this paper is to raise awareness of the benefits of wellness programs for contemporary organizations and aids in tackling workplace bullying. Design/methodology/approach: This study used a qualitative design and employs a new empirical approach to tackle workplace bullying. With over a hundred working professionals engaged in focus groups and facilitation methodologies for a total of five workshops and 60 hours, this study suggests a new framework for intervening in workplace bullying that considers workplace wellness as a system. Findings: The findings revealed that these professionals perceived workplace wellness as a formidable component of the health and success of employees, organizations, and community, and perceived workplace bullying as a serious threat to physical and mental wellness. Employee participation and involvement in the design of workplace wellness programs was viewed as essential to the success of these programs in organizations. Research limitations/implications: This research has implications as it expands understanding and discovery into what aids employees to reduce their stress, fatigue, anxiety, and other conditions that lead to conflict or bullying in workplaces. It gives attention to a system of wellness that is vital to people and their organizations. Practical implications: Study participants consistently asserted their desire to be active participants in establishing workplace wellness programs that effectively address workplace bullying, systems that enhance safety, and health. Social implications: This study highlights the role organizations play in shaping individual and community physical and mental well-being, health, and safety through effective workplace wellness programs. Originality/value: This study should be helpful to organizations and researchers looking to address workplace wellness, safety, and bullying in a context broader than just liability and the cost savings of employee physical health, and may further add to the discussions of workplace wellness policy and regulation.